Alokasi Air dan Pengembangan Prasarana Penyediaan Air Baku di DAS Ciliman - Isvan Taufik; Muhammad Yanuar J. Purwanto; Bambang Pramudya; Satyanto K. Saptomo (Jurnal Ilmu Lingkungan, 2020)
Ciliman Watershed is one of the second largest watersheds in Banten Province and is part of the Ciliman-Cibungur River Region, besides being a rice barn in Banten Province, its development has accelerated since the development of Panimbang Airport, Tanjung Lesung Special Economic Zone, and Serang Toll Road Development –Considering. Therefore, it is necessary to regulate the water allocation for various needs and the possibility of developing water supply infrastructure. WEAP is one of the hydrological software in evaluating and planning the water balance of a region. The WEAP approach method operates with the basic principle of water balance and allows the creation of scenarios based on existing conditions to investigate the impact of policies or alternative assumptions in the use and availability of water in the future.The purpose of this study includes; (1) Analyzing the potential availability of raw water in each Ciliman Sub-watershed, (2) Analyzing the raw water needs of the Ciliman watershed, (3). Analyzing water allocation for each raw water requirement in the Ciliman watershed to be fulfilled and (4). Analyzing the potential for developing raw water infrastructure in the Ciliman watershed. The types of data used in this study are secondary data including: (1) monthly rainfall data from the Ciliman reservoir rainfall observation station, Gunung Kencana, Bojong Manik and KP3 at year 1998 - 2015, (2) population data of Ciliman watershed region, (3) the amount of raw water needs data, (4) Irrigation networks around the Ciliman watershed data (5) maps of the Ciliman watershed, (6) Tools used in this study include computer units and WEAP software. The method used in this study basically is the water allocation based on the water balance and determining the order of priority needs. The results analysis obtained that based on 5 scenarios with 3 alternative dam construction the most optimal use of water is fifth scenario with the development of  an agricultural area of 3,200 ha and an average electricity generation potential of 0.96 MW in a year.